SOCIAL CUSTOMER RELATIONSHIP MANAGEMENT SEBAGAI STRATEGI BISNIS PADA BANK (STUDI KASUS DI BANK BPD DIY) - Putri Taqwa Prasetyaningrum; Irya Wisnubhadra; Suyoto Suyoto (Jurusan Teknik Informatika, 2016)
Social CRM is designed to engage the customer in a collaborative conversation in order toprovide mutually beneficial value. BPD DIY main branch office located in the middle of the cityhas a growing number of borrowers from 2013 until 2014 a number of 4.3% and there is areduction in the number of accounts under 1%. Therefore the Bank BPD DIY are required togive priority to the quality of service on the client. Inthis study, SCRM application made for theusers, in this case to improve relationships and quality of service on customer serviceone customer complaints against Banks in a timely, accurate and effective. The method used isthe method of software development methodologies thatmany developed waterfall. Thisresearch resulted in SCRM system to establish relationship with customer throughpemanfaatan web 2.0 technologies and introduces different approaches in establishingrelationships with customer relations especially in regarding the complaint of the customerthrough the social web in order to improve the quality of service to customers andretain existing clients as well as making one of the SCRM applications to support the businessstrategy of the company. Based on the results of development on SCRM on BPD DIY,softwarehas been successfully developed in accordance with predetermined functionality